Sistem Pertanian Terpadu Dengan Sistem Kandang Paddock Untuk Meningkatkan Pendapatan - Evi Warintan Saragih; Bernadetta Wahyuni; F.H. Listyorini (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Integrated farming system is a combination of two or more agriculture activities in the same areal. Papuan people who lived in Bremi village have agriculture systems where planting plant and raising an animal are two different activities and shoud be in the different place. This agriculture system cause many problems such as social conflict and environmental problem. Integrated farming system with paddock cage and rotation system is new agriculture concept for Papuan. This new concept could become an alternative solution to the problem and expected to increase the income. Integration of poultry and vegetable farming with paddock system may become a solution to social conflict and environmental problems that occur in the Bremi village. The intergated farming system have many benefit such us reduced tension between farmer, avoid shifting cultivation system that protect the forest and increase the income